Metal coordination sphere deformation induced highly Stokes‐shifted, ultra broadband emission in 2D hybrid lead‐bromide perovskites and investigation of its origin - Febriansyah, Benny (2020)
Published studies of layered (2D) (100)‐oriented hybrid lead‐bromide perovskites evidence a correlation between increased inter‐octahedral (Pb‐Br‐Pb) distortions and the appearance of broadband white light emission. However, the impact of distortions within their constituent [PbBr6]4− octahedra has yet to be assessed. Herein, we report two new (100)‐oriented 2D Pb‐Br perovskites, whose structures display unusually high intra‐octahedral distortions, whilst retaining minimal inter‐octahedral distortions. Using a combination of temperature‐dependent, power‐dependent and time‐resolved photoluminescence spectroscopic measurements, we show that increased intra‐octahedral distortion induces exciton localization processes and leads to formation of multiple photoinduced emissive colour centres. Ultimately, this leads to highly Stokes‐shifted, ultrabroad white light emission at room temperature.